HUBUNGAN POLA MAKAN DENGAN TERJADINYA HIPERTENSI PADA PASIEN HIPERTENSI DI RUMAH SAKIT PTPN II BANGKATAN BINJAI TAHUN 2017 - Suarni, Leny (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2017)
A healthy diet is eating foods that contain calories and nutritional needs according to our daily needs. Therefore, each person's healthy eating patterns are actually not the same. Hypertension is a condition where systolic blood pressure is more than 120 mmHg and diastolic pressure is more from 80 mmHg (Muttaqin, 2009). The purpose of this study was to determine the relationship between eating patterns and the occurrence of hypertension in hypertensive patients at PTPN II Bangkat Binjai Hospital in 2016. The researcher involved two variables. (Hidayat, 2008) The population in this study were all patients who experienced hypertension disease treated at PT Departure II Hospital Bangkat Binjai, amounting to 20 people. The sample in this study was the entire population of patients suffering from hypertension at PTPN II Hospital Binjai Departure in 2016 with saturated sampling techniques. The results of this study indicate that the relationship of eating patterns with the occurrence of hypertension in hypertensive patients at PTPN II Hospital Bangkatan Binjai in 2017. It is expected that patients can prevent hypertension by maintaining their daily diet, exercise, and adequate rest.Keywords: Hypertension and dietary habit